The antibacterial and antibiofilm efficacies of a liposomal peptide originating from rice bran protein against Listeria monocytogenes. Issue 11 (12th October 2017) - Pu, Chuanfen; Tang, Wenting
Abstract : A liposomal peptide (Lys-Val-Asp-His-Phe-Pro-Leu) originating from rice bran protein exhibits antibacterial and antibiofilm efficacies against Listeria monocytogenes . Abstract : With the aim of exploring a natural antilisterial peptide from food-derived origin, an antibacterial peptide named as Alpep7 was purified from the bromelain hydrolysate of rice bran protein (RBP) in this study. The resulting amino acid consequence was identified as KVDHFPL (Lys-Val-Asp-His-Phe-Pro-Leu) by ultraperformance liquid chromatography tandem matrix-assisted laser desorption/ionisation quadrupole time-of-flight mass spectrometry (MALDI Q-TOF MS). In addition, to assess the probability of the targeted delivery of liposome encapsulation of the peptide to Listeria biofilm, Alpep7-loaded liposomes were further prepared from a mixture of dipalmitoylphosphatidylcholine, stearylamine and cholesterol in a molar ratio of 10 : 3 : 2 and characterised by the analysis of particle size, zeta potential, microtopography and storage stability. The results showed that the liposomes exhibited a well-defined spherical shape, with an average diameter below 200 nm. The liposomes maintained favourable stability after storage at 4 °C for 4 weeks. Comparisons between the activities of free and liposomal Alpep7 via microbroth dilution, regrowth analysis and confocal scanning laser microscopy suggested that liposomal delivery was more effective during the initial exposure of the liposomes to the biofilms. The thermodynamic analysis indicated that the adsorption of liposomal Alpep7 to the listerial biofilm was a spontaneous, exothermic process. The results may provide a natural means for the treatment of listerial contamination and guide the potential application of liposomes for the targeted delivery of antimicrobials to pathogenic biofilms in the food industry.